STUDENTS’ SPEAKING MOTIVATION THROUGH WORD ASSOCIATION - Muhammad Zakaria; Mohamad Sahil (ENGLISH, 2018)
This research was conducted to know the kinds of intrinsic and extrinsic motivation that students have when learning through word association game and the student’s attitude performed. In conducting this research, the researcher used qualitative design. The data were collected through questionnaires and observations. The participants of this research were 28 students. The result of this research showed that the kinds of intrinsic motivation that the students showed on their desire (82.14%) could be seen from the aspects of happy, curious, and interested in learning speaking using game. The second intrinsic motivation showed in learning speaking using game was their interest (71.43%). The students needed the game because it was useful, relevant with their need, appropriate with the lesson and they could achieve the learning outcomes (85.72%). The last, the students had intrinsic motivation of goal (78.57%) and it could be seen from their understanding and mastered the lesson successfully, found new vocabulary and implemented the moral value from game. Furthermore, they had extrinsic motivation and it could be seen. From the fact that for the teacher did not only teach the lesson but also supported and made in learning process easier, their parents gave support to learn English and the classroom was comfortable to learn (92.86). The students’ attitude was shown from the fact that they understood the content of game and they answered teachers’ question correctly and actively. From the result, the researcher concluded that using game influenced students’ motivation in learning speaking using game and the students’ attitudes are positive.